CULINARY SIMPLICITY & VISITOR LOYALTY AT WARUNG MAK YAH IN COASTAL AREA BATAM - Lubis, Arina Luthfini; Cahayani, Kartika; Santika, Kamelia (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
This study aims to analyze how culinary simplicity contributes to the formation of customer loyalty at Warung Mak Yah, located in the coastal area of Nongsa, Batam. The phenomenon of high visitation frequency at a modest breakfast stall with limited facilities and minimal menu variations serves as the primary background of this research. The study employs a qualitative approach using an exploratory case study method. Data were collected through direct observation, in-depth interviews with the owner and customers, and documentation, and were analyzed using thematic analysis to identify patterns and meanings emerging from customer experiences. The findings indicate that customer loyalty is formed through a combination of taste consistency, the emotional experience created by the coastal atmosphere, close social interaction, and perceived affordability. Taste consistency (28%) and coastal ambiance (27%) emerged as the dominant factors influencing repeat visits, while social interaction (18%) and affordable pricing (18%) functioned as supporting factors, and menu simplicity (9%) was perceived as an acceptable characteristic within the context of a simple breakfast stall. This study concludes that in small-scale local culinary businesses, customer loyalty is shaped more by authentic experiences and consistent quality than by product complexity or modern facilities. The findings contribute to the literature on consumer loyalty within local culinary contexts based on experiential and relational dimensions.